2020
DOI: 10.30721/fsab2020.v3.i1.46
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical composition and antioxidant activity of Malus baccata (L.) Borkh. fruits

Abstract: Crab apple (Malus baccata (L.) Borkh.) was mainly distributed in Europe as an ornamental plant, but the nutritional properties of its edible fruits were not fully revealed. The aim of the current study was to characterize the phytochemical composition of ripen carb apple fruits and to evaluate their nutritional and antioxidant potentials. The fruits were assayed for moisture and ash content, proteins, lipids, carbohydrates, titratable acidity (TA), pH, total phenolic compounds and natural pigments. Among the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Michev et al (1983) reported that total lipid content expressed as ether extract was in the range 0.5-1.85% for other Sorbus aria fruit. The lipid content of whitebeam fruit was lower than that of Sea-buckthorn fruit -6.20-3.60% (Zenkova and Pinchykova, 2019), but higher in Malus baccata -0.55 ±0.05% dw (Petkova et al, 2020).…”
Section: Nutritional Characteristics Of Common Whitebeam (Sorbus Aria) Fruitmentioning
confidence: 70%
See 3 more Smart Citations
“…Michev et al (1983) reported that total lipid content expressed as ether extract was in the range 0.5-1.85% for other Sorbus aria fruit. The lipid content of whitebeam fruit was lower than that of Sea-buckthorn fruit -6.20-3.60% (Zenkova and Pinchykova, 2019), but higher in Malus baccata -0.55 ±0.05% dw (Petkova et al, 2020).…”
Section: Nutritional Characteristics Of Common Whitebeam (Sorbus Aria) Fruitmentioning
confidence: 70%
“…We did not detect any monomeric anthocyanidins in the fruit of S. aria (Table 2). The absence of monomeric anthocyanidins was found for the fruit of crab apple (Petkova et al, 2020).…”
Section: Natural Pigmentsmentioning
confidence: 95%
See 2 more Smart Citations
“…There are only a few reports on carbohydrate composition in the fruit of the Siberian crabapple, M. baccata (L.) Borkh. [22,23]. In addition to being of fundamental interest, the knowledge of the characteristics of the carbohydrate composition of wild Malus species may be useful for their use as sources of genetic variability for apple breeding.…”
Section: Introductionmentioning
confidence: 99%